The Influence of Career Development on Employee Performance with Organizational Commitment as a Mediator among MSMEs on Kusumanegara Street, Yogyakarta - Asy, Martinus Andika; Kurniawan, Ignatius Soni; Lysander, Mohammad Ahyar Syafwan (JURNAL MANAJEMEN MOTIVASI, 2026)
Career development is vital in human resource management, yet often lacks systematic implementation in micro, small, and medium enterprises (MSMEs), including those on Kusumanegara Street, Yogyakarta. This study examines the effect of career development on employee performance, with organizational commitment as a mediating variable. Using questionnaire data from MSME employees and SmartPLS 4 for analysis, results show that career development significantly influences both organizational commitment and performance. However, organizational commitment does not significantly affect performance nor mediate the relationship. These findings suggest MSMEs should adopt strategies that foster an optimal work environment to enhance employee performance.